The effects of cold-restraint stress on urinary bladder wall compared with interstitial cystitis morphology - ERCAN, FERİHA (SPRINGER VERLAG, 1999)
Stress is associated with many diseases of unknown aetiology. This study demonstrates the effects of cold-restraint stress on the morphology of the urinary bladder. Additionally, it compares the results obtained with the morphology of the interstitial cystitis. The animals were subjected to three hours of cold-restraint stress and then starved for 48 h. The morphology and histochemistry of the urinary bladder was investigated with light and electron microscopy. The proliferative activity was analysed via flow cytometry. Increased and degranulated mast cells in the mucosa, leucocyte infiltration in the lamina propria, vacuole formation in the urothelial cells, loose tight junction, dilated intercellular spaces and altered proliferative activity were observed in the stress group when compared with the control. The increase in the number of mast cells and especially degranulated mast cells and vacuole formation and the loose tight junction of the urothelium correlated with the histopathological findings of interstitial cystitis.
Keywords: cold-restraint stress; urinary bladder; interstitial cystitis; mast cell; urothelium; ultrastructure; ruthenium red; flow cytometry; EPITHELIAL PERMEABILITY BARRIER; MUCOSAL MAST-CELLS; SURFACE GLYCOSAMINOGLYCANS; HISTAMINE; RATS; PROLIFERATION; GLUTATHIONE; ACTIVATION; BACTERIAL; RELEASE